2.45 GHz Wi-Fi band operated circularly polarized rectenna for RF energy harvesting in smart city applications. Issue 3 (11th February 2022) - Surender, Daasari; Halimi, Md. Ahsan; Khan, Taimoor; Talukdar, Fazal A.; Koul, Shiban K.; Antar, Yahia M.M.
Abstract : This article proposes a single band circularly polarized (CP) rectenna operate at a 2.45 GHz Wi-Fi band, using a hexagonal shape of a microstrip radiator and a voltage doubler rectifier for smart city applications. A partial ground plane embedded with isosceles triangular slot and notch helps in obtaining the desired resonance characteristics with improved antenna performance and reasonable miniaturization. Two crossed-slots, introduced into the radiating patch, yield CP characteristics. Also, the proposed antenna shows an omnidirectional radiational behavior that helps in harvesting RF energy from all of its surroundings. A voltage doubler configuration using the SMS7630-005 LF diode is chosen for designing a rectifier circuit to achieve a maximum conversion efficiency of 65.1% and an output voltage of 1.65 V at an input power of 0 dBm for the load resistance value of 4.1 kΩ which is very much suitable for powering low power sensing devices.